The Effect of Empowerment Leadership on Employee Intrinsic Motivation With Psychological Empowerment as an Intervening Variable in the Binjai City Environment - Rukun; Abdi Sugiarto (International Journal of Society and Law, 2024)
Empowerment leadership, which provides authority and support to subordinates, will improve employee intrinsic motivation as well as organizational performance. The purpose of this study is to find out and analyze the influence of Empowerment Leadership on Intrinsic Motivation mediated by Psychological Empowerment at the Binjai City Environmental Office. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 75 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) showed that empowerment leadership did not have a significant influence on intrinsic motivation (T-statistic 0.985 < 1.96; P-value 0.328 > 0.05), which indicates that improving empowerment leadership does not directly increase employee intrinsic motivation. However, empowerment leadership had a positive and significant effect on psychological empowerment (T-statistic 43,372 > 1.96; P-value 0.000 < 0.05), indicating that improved empowerment leadership significantly improved employee psychological empowerment. Furthermore, psychological empowerment had a positive and significant effect on intrinsic motivation (T-statistic 4.848 > 1.96; P-value 0.000 < 0.05), which means that increased psychological empowerment significantly increases intrinsic motivation. Indirect influence analysis showed that psychological empowerment was able to intervene in the influence between empowerment leadership and intrinsic motivation (T-statistic 4.747 > 1.96; P-value 0.000 < 0.05). These findings provide insight that psychological empowerment plays a significant mediator role in the relationship between empowerment leadership and intrinsic motivation, emphasizing the importance of psychological empowerment in increasing employee intrinsic motivation.